Exosomes from CD133+ human urine-derived stem cells combined adhesive hydrogel facilitate rotator cuff healing by mediating bone marrow mesenchymal stem cells - Xiaopeng Tong; Yan Xu; Tao Zhang; Chao Deng; Jinrui Xun; Deyi Sun; Daqi Xu (Journal of Orthopaedic Translation, 2023)
Background: The inadequate regeneration of natural tissue (mainly fibrocartilage) between tendon and bone during rotator cuff (RC) repair results in an unsatisfactory quality of RC healing. Cell-free therapy based on stem cell exosomes is a safer and more promising approach for tissue regeneration. Here, we investigated the effect of exosomes from human urine-derived stem cells (USCs) and their subpopulations (CD133+USCs) on RC healing. Methods: USCs were isolated from urine and sorted by flow cytometry to obtain CD133+ urine-derived stem cells (CD133+ USCs). Urine-derived stem cell exosomes (USC-Exos) and CD133+ urine-derived stem cell exosomes (CD133+ USC-Exos) were subsequently isolated from the cell supernatant and identified by transmission electron microscopy (TEM), particle size analysis, and Western blot. We performed in vitro functional assays to evaluate the effects of USC-Exos and CD133+ USC-Exos on human bone marrow mesenchymal stem cells (BMSCs) proliferation, migration, osteogenic differentiation, and chondrogenic differentiation. In vivo experiments were performed by local injection of exosome–hydrogel complexes for the treatment of RC injury. The effects of CD133+ USC-Exos and USC-Exos on RC healing were assessed from imaging, histological, and biomechanical tests. Results: CD133+ USCs were positive for CD29, CD44, CD73, CD90, CD133, but negative for CD34 and CD45. Differentiation ability test results showed that both USCs and CD133+ USCs had the potential for osteogenic, chondrogenic, and adipogenic differentiation, but CD133+ USCs had stronger chondrogenic differentiation ability. CD133+ USC-Exos and USC-Exos could be efficiently taken up by BMSCs and promote their migration, osteogenic and chondrogenic differentiation. However, CD133+ USC-Exos could promote the chondrogenic differentiation of BMSCs more than USC-Exos. Compared with USC-Exos, CD133+ USC-Exos could promote the healing of bone-tendon interface (BTI) more effectively, which might be related to its ability to promote the differentiation of BMSCs into chondroblasts. Although the two exosomes exhibited the same effect in promoting subchondral bone repair in BTI, the CD133+ USC-Exos group had higher histological scores and stronger biomechanical properties. Conclusion: CD133+ USC-Exos hydrogel complex may become a promising therapeutic approach for RC healing based on stem cell exosomes. The translational potential of this article: This is the first study to assess the specific role of CD133+ USC-Exos in RC healing which may be related to the activation of BMSCs by CD133+ USC-Exos towards chondrogenic differentiation. Further, our study provides a reference for possible future treatment of BTI by applying CD133+ USC-Exos hydrogel complex.